A three-dimentional kinematics on contribution of effective lower body segment rotations in producing foot velocity in soccer volley kicking - Sugni, S.; Nunome, H.; Tamura, Y.; Iga, T. (ISBS Proceedings Archive (Michigan), 2017)
The purpose of this study was to illustrate the contribution of lower body segment rotations in producing foot velocity of soccer volley kicking. Ten experienced male university soccer players conducted to kick balls in varied heights. Their kicking motions were captured at 500 Hz. According to the procedure of Sprigings et al (1994), the effectiveness of pelvis and hip, knee and foot joint rotations in producing forward and vertical velocities of the foot centre of gravity were computed. Apparent unique contribution of the pelvis horizontal rotation to the forward foot velocity, and of the pelvis frontal and the hip internal rotations to the upward foot velocity were observed in volley kicking. These results endorsed the findings of Sugi et al (2016a) regarding emphasized joint motions during soccer volley kicking.